2013
DOI: 10.1166/jon.2013.1030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Effect of Chirality of Carbon Nanotube on the Interfacial Thermal Resistance

Abstract: Concentrated Solar Power (CSP) systems are used widely as a stable and reliable renewable source of energy. However, intermittency of this power source and the variability in demand for electrical power creates challenges that necessitate the integration with energy storage for reliable dispatch of power. Thermal Energy Storage (TES) systems provide a cheap, cost-effective and reliable option for energy storage in renewable power delivery systems. Due to their low vapor pressures at elevated temperatures, molt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Salt ions are ordered around nanoparticles due to electrostatical interactions, forming fractal-like structures. The semisolid layering approach is in accordance with the increment observed in Cp and the available nanoparticle surface area; however, more experimental work is needed in order to check and refine the model [ 21 - 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salt ions are ordered around nanoparticles due to electrostatical interactions, forming fractal-like structures. The semisolid layering approach is in accordance with the increment observed in Cp and the available nanoparticle surface area; however, more experimental work is needed in order to check and refine the model [ 21 - 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The effects of different types of CNT have been investigated on some fluid properties in some works. [7][8][9][10] The effects of the chiral vector of a CNT on the center of mass mean velocity of a water nanodroplet confined inside the CNT by a thermal gradient along the axis of the CNT were investigated by Zambrano et al 7 It was concluded that the center of mass mean velocity of a water nanodroplet in different thermal gradients is decreased by changing the type of CNT from armchair to chiral and then to zigzag. Binesh and Kamali 8 investigated the effects of chirality of CNTs on single-file water permeation through CNT membranes.…”
Section: Introductionmentioning
confidence: 99%